Chronic lithium toxicity - Babulovska, Aleksandra; Bekjarovski, Niko; Petkovska, Lidija; Pereska, Zanina; Simonovska, Natasha; Naumoski, Kiril; Kostadinoski, Kristin; Ristova, Biljana (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2024)
Objective: Lithium toxicity can be acute or chronic and the effects may be disabling or life-threatening. We present a case with lithium toxicity due to chronic treatment. A 63-year-old man was brought to the University Clinic for Toxicology in Skopje with a 2-day history of confusion, slurred speech, nausea, vomiting, loss of appetite, and weakness. His medical history included bipolar disorder, which had been diagnosed 17 years previously, and since then he has been on lithium therapy 900mg orally daily. The patient had not had regular check-ups for several years. His oral intake was markedly reduced, for the last five days. On admission, he was severely dehydrated. Vital signs included a blood pressure of 110/50 mm Hg a pulse rate of 49 beats/min, and oxygen saturation of 97%. Investigations revealed serum lithium level 3.43 (normal 0.5–1.5 mmol/L) suggesting lithium toxicity, creatinine level 168 umol/L, urea 15 mmol/L alkaline phosphatase 182 U/L calcium 2.34 mmol/L. A 12-lead electrocardiogram showed normal sinus rhythm, precordial T-wave inversions, and a prolonged QTc interval of 533 ms. After one treatment of hemodialysis lasting two and half hours, his lithium level dropped to 2,04 mmol/L and creatinine to126 μmol/L. No intracranial abnormality was seen on a computed tomography scan of the head. Further investigation revealed parathyroid hormone 170 pg/ml, ionized calcium 1.43 mmol/L. Treatment management included volume replacement for dehydration. Abdominal computed tomography was with orderly finding. All investigations were at the normal therapeutic range before discharge and sent to the psychiatrist on the eleventh day. Conclusion: Patients on long-term lithium therapy with no regular check-ups are at high risk of developing toxicity. The toxicity was due to intravascular volume depletion, and impaired lithium excretion. The patients should be monitored frequently for all potential endocrine, renal, and neurological disorders.
Keywords: lithium; toxicity; parathyroid hormone